2005
DOI: 10.1016/j.icesjms.2005.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change on the adaptation of marine fish in the Baltic Sea

Abstract: The biota in the Baltic Sea has formed under wide variations in environmental conditions induced by climate change since the last glaciation. Areas of the Baltic Sea display marked differences in salinity, oxygen content and temperature of water layers, timing of the peak production cycle, and other basic environmental conditions. Some of the most important adaptations of marine fish to the conditions in the Baltic Sea facilitate reproduction at low and changeable salinity and oxygen deficiency in deeper layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…Deep-water oxygen concentration and cod yearclass strength were clearly correlated during the period from 1958 to 1988 (Jansson, 2003). The expansion of oxygendeficient bottom water has caused strong shifts within the food web so that marine fishes (cod, sprat, herring) are impacted by both a loss in spawning area and a change of prey spectra in the Baltic Sea (Ojaveer and Kalejs, 2005). Commercial fisheries follow these changes, but normally with a phase-delay of a few years to adapt fishing gear and method.…”
Section: Baltic Seamentioning
confidence: 99%
“…Deep-water oxygen concentration and cod yearclass strength were clearly correlated during the period from 1958 to 1988 (Jansson, 2003). The expansion of oxygendeficient bottom water has caused strong shifts within the food web so that marine fishes (cod, sprat, herring) are impacted by both a loss in spawning area and a change of prey spectra in the Baltic Sea (Ojaveer and Kalejs, 2005). Commercial fisheries follow these changes, but normally with a phase-delay of a few years to adapt fishing gear and method.…”
Section: Baltic Seamentioning
confidence: 99%
“…The colonisation by marine species in the Baltic Sea is believed to have been achieved as a result of specific adaptations to life in a marginal environment (e.g. Ojaveer & Kalejs 2005). In the North Sea-Baltic Sea transition zone salinity levels are expected to exert a significant selective pressure on local populations although other environmental factors, such as temperature dynamics, are also expected to play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that Baltic (Atlantic) cod Gadus morhua L. tolerate lower salinities during egg fertilisation and the egg phase compared with populations from the Skagerrak (Nissling & Westin 1997). Timing of spawning also seems to conform to spatial and temporal production peaks (Tomkiewicz et al 1998, Ojaveer & Kalejs 2005.…”
Section: Introductionmentioning
confidence: 99%
“…KEY WORDS: Sprat · Overwintering · 'Rise and sink' swimming · Schooling · Ice cover 464: 245-256, 2012 Populations of sprat are also present in environments that may be covered with ice, e.g. the Baltic Sea and some Norwegian fjords (Ojaveer & Kalejs 2005, Casini et al 2006). Ice will affect not only light conditions, but also the ability for this physostome fish to ascend to the surface for gulping air in order to fill its swimbladder (Blaxter & Batty 1984).…”
mentioning
confidence: 99%